Impact of COVID-19 on health services utilization in Province-2 of Nepal: a qualitative study among community members and stakeholders - Singh, DR; Sunuwar, DR; Shah, SK; Karki, K; Sah, LK; Adhikari, B; Sah, RK (BioMed Central, 2021)
Background The COVID-19 pandemic has posed unprecedented challenges and threats to the health care system, particularly affecting the effective delivery of essential health services in resource-poor countries such as Nepal. This study aimed to explore community perceptions of COVID-19 and their experiences towards health services utilization during the pandemic in Province-2 of Nepal.